Nutritional Condition Characterization of Children Under 5 Years Old with Congenital Heart Disease - Yan González Ramos; Annia Quintana Marrero; Nancy González Vales; Anaelys Acosta Hernández; Belkis González Aguiar (Universidad de las Ciencias Médicas de Cienfuegos, 2017)
Foundation: congenital heart disease is the most frequent anomaly at birth and causes 20 % of neonatal deaths. The haemodynamic alterations presented in these cases affect their nutritional condition and cause complications related to postoperative survival. Objective: to characterize the nutritional condition of children under 5 with congenital heart disease. Method: a descriptive, correlational and cross - sectional study was carried out in patients younger than 5 years old with congenital heart disease at the Cienfuegos cardiopathy clinic. The following variables were used: age, sex, type of heart disease and nutritional evaluation. The information was processed using the statistical package SPSS 19, proceeding to the analysis and discussion of those results that were shown in tables, graphs and percentages. Results: acyanotic heart disease was the most frequent, representing 2/3 of the total. Males and children older than 1 year were those with the greatest nutritional problems. 10.5 % of the studied patients had low birth weight. 97.4 % of the patients with low height were in the stage of homeorhesis associated with acyano- genic cardiopathies with increased pulmonary flow. The biochemical parameters did not present great affectation. Conclusion: nutritional condition is frequently affected in children with congenital heart disease, which has declined in recent years thanks to prenatal diagnosis of critical heart disease, where survival is minimal.